THE POSSIBILITY OF STUDYING SUPERSONIC FLOW PROFILE CLOSE TO THE SCREEN BY THE METHOD OF HYDRAULIC ANALOG MODELING - D. T. Aliakbarov; A. A. Kukin; V. V. Trofimov (Научный вестник МГТУ ГА, 2018)
Supersonic flow around the system of bodies (lattice wings, a wing near the shielding surface, blades of supersonic stages of the compressor, etc.) is accompanied by complex pictures of shock waves, which depend on several parameters characterizing the mutual arrangement, the bodies of their external shapes and sizes, as well as the Mach number. These patterns are determined by the nature of the interaction of the head shock wave and the shock wave on the lower surface of the profile, caused by a change in the flow direction as a result of deflection of the flap.The paper presents the results of an investigation of supersonic flow around a profile with a flap near the screen, obtained using the method of hydraulic analog simulation (the method of gas-hydraulic analogy). This method is based on the analogy of the equations of motion describing a planar gas flow and a thin liquid layer and is used in solving a large class of plane problems of stationary and nonstationary gas dynamics.The parameters that affect the structure of the flow around the profile near the screen are: the Mach number of the profile movement with the values M∞ = 1.4 ÷ 1.9; relative distance of the profile from the screen with the values Нз = 0.2 ÷ 1.0; angle of flap deflection with values δз = 0 ÷ 40°. In the course of the experimental investigation, the changes in the structure of shock waves were determined and the influence of the above-mentioned parameters on the process was revealed. The results of the experimental study are presented in the form of graphical dependencies of the relative position of the shock wave on the lower surface of the profile for different Mach numbers, the relative position of the profile from the screen, and the angle of deflection of the flap Δ = f (М∞,Нз , δз). On the basis of the analysis of the obtained dependences, a generalized parameter is derived, which makes it possible to determine the boundaries of changes in the structure of shock waves in a given type of problem.